ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Sidauruk, Tagor Darius; Nainggolan, Adolpino; Putri Zaihani (Jurnal Liabilitas, 2024)
The aim of this research is to determine the influence of taxpayer awareness, tax sanctions and implementation of the e-filling system on individual taxpayer compliance The population in this study were all employees at PT Paragon Technology and Innovation. Sampling was taken using the Slovin formula as many as 80 samples that had NPWP. The research results were obtained by using multiple linear regression analysis methods. The results of this research show that Tax Sanctions and the Implementation of the E-Filing System have a significant effect on Individual Taxpayer Compliance, and are not influenced by taxpayer awareness.